Polyamines and Hypusination Are Required for Ebolavirus Gene Expression and Replication - Michelle E. Olsen (American Society for Microbiology, 2016)
ABSTRACT Ebolavirus (EBOV) is an RNA virus that is known to cause severe hemorrhagic fever in humans and other primates. EBOV successfully enters and replicates in many cell types. This replication is dependent on the virus successfully coopting a number of cellular factors. Many of these factors are currently unidentified but represent potential targets for antiviral therapeutics. Here we show that cellular polyamines are critical for EBOV replication. We found that small-molecule inhibitors of polyamine synthesis block gene expression driven by the viral RNA-dependent RNA polymerase. Short hairpin RNA (shRNA) knockdown of the polyamine pathway enzyme spermidine synthase also resulted in reduced EBOV replication. These findings led us to further investigate spermidine, a polyamine that is essential for the hypusination of eukaryotic initiation factor 5A (eIF5A). Blocking the hypusination of eIF5A (and thereby inhibiting its function) inhibited both EBOV gene expression and viral replication. The mechanism appears to be due to the importance of hypusinated eIF5A for the accumulation of VP30, an essential component of the viral polymerase. The same reduction in hypusinated eIF5A did not alter the accumulation of other viral polymerase components. This action makes eIF5A function an important gate for proper EBOV polymerase assembly and function through the control of a single virus protein. IMPORTANCE Ebolavirus (EBOV) is one of the most lethal human pathogens known. EBOV requires host factors for replication due to its small RNA genome. Here we show that the host protein eIF5A in its activated form is necessary for EBOV replication. We further show that the mechanism is through the accumulation of a single EBOV protein, VP30. To date, no other host proteins have been shown to interfere with the translation or stability of an EBOV protein. Activated eIF5A is the only protein in the cell known to contain the specific modification of hypusine; therefore, this pathway is a target for drug development. Further investigation into the mechanism of eIF5A interaction with VP30 could provide insight into therapeutics to combat EBOV.